Aktywność kulturalna w kontekście życia rodzinnego, społeczno-politycznego i zasad moralnych - Krzysteczko, Henryk (Studia Pastoralne, 2007)
One of the most significant goals of community life and social development is creating and passing on cultural achievements to future generations (Christifideles laici, 44) which in turn makes human life better, both in terms the of individual and the community (Gaudium et spes, 53). The paper presents the results of surveys carried out in order to find the relations between cultural activity and family life, as well as local and parish community life. The project was conducted by the Silesian University and it was supported by the Regional Local Authorities of the Silesian Region. A group of 1030 women was chosen for the survey. Two extreme groups were selected: the first group featured low cultural activity whereas the second group had considerable cultural involvement. The results were compared regarding various aspects of family and community life. The results revealed that, in terms of the priesthood, there is a favorable correlation between cultural activity, family and community life. High cultural activity also improves family life satisfaction and the feeling of security among family members. However, the survey has also revealed that there can be a negative correlation between cultural activity and moral principles concerning marriage and love in the family. The survey results showed the negative influence of liberal ideology. Some liberal principles, such as tolerance, led to accepting uncritically any kinds of divergence including homosexual relations, abortion and divorce. It seems that culture in the broad meaning of the word, with all its aspects and the people involved in particular, lost its basic dimension and depth. This is contrary to John Paul II’s preaching that moral principles are fundamental in any kind of cultural activity. The obtained results require further detailed research so that positive aspects and trends in contemporary culture can be examined and highlighted. A new approach to find ways of implementing and respecting moral principles regarding marriage and family should be looked for, since that is the only natural and indispensable environment for the development of any individual.